Empowering writing techniques: Hand In Hand Initiative (HIHI) workshop to achieve writing and publishing goals/ Nurul Ilham Adam ... [et al.] - Adam, Nurul Ilham; Taib, Nurul Izza; Mohamed, Siti Mazleena; Abdul Wahab, Rabiatul Adawiyah; Abdul Aziz, Rosmawati; Mohd Noor, Adibah; Mohamed Khir, Northaqifah Hasna; Hasmi, Nur Atirah (Universiti Teknologi MARA, Perak, 2023)
A Hand in Hand Initiative (HIHI) Workshop was successfully organized at the Faculty of Applied Science (FSG) UiTM Perak Branch Tapah Campus on 15th April 2023. The course was designed to address some of the challenges that lecturers encounter in the writing and publishing industries because of the highly challenging teaching and learning professions that are currently in place. Additionally, the Hand in Hand Initiative program approaches writing and publishing holistically, offering advice for managing the publishing industry in addition to concentrating on improving writing abilities.